Retour sur le récit de soi. Quels liens entre l’enquête ethnographique ou sociologique, le témoignage et l’autofiction ou l’autobiographie littéraire ? - Fabien Truong (Contextes, 2025)
This interview analyses how trajectories of class defectors are usually narrated, insisting on what distinguishes ethnographic narratives based on supported reflexivity from autobiographical narratives based on embodied reflexivity or from journalistic narratives following a repetitive "media script". If the trajectories of defectors are particularly conducive to feeding the hybridity between distinct forms of narratives, one nevertheless tends to observe redundancy: recurrent staging of "school-centered" trajectories, tendency to insist on/reformulate the past to the detriment of the present, insistence on the feeling of betrayal and illegitimacy. Conversely, contemporary ethnographic works show that there are also, within these trajectories, numerous movements and displacements which do not refer to the sole logic of division, as the author recalls with the metaphor of the "rocking horse", forged during one of his previous fieldworks.